The incidence of malignant infiltration in human osteosarcoma biopsy tract - Roa, Mohana (2006)
Background: Osteosarcoma is the most common non-haemopoetic primary bone malignancy afflicting the young. Biopsy remains the gold standard in the confirmation of the diagnosis. The placement of the biopsy is of utmost importance as the tract is removed en bloc with the tumour during limb sparing surgery, with the assumption that it is contaminated by the tumour. Tissue conservation, to ensure adequate soft tissue cover, and preservation of function still remains a challenge for musculoskeletal oncology surgeons. This study aims to investigate the incidence of tumour infiltration in osteosarcoma biopsy tract, namely in the pseudocapsule, surrounding muscle, fascia, subcutaneous tissue and skin; in order to explore the margin of tumour infiltration for safe resection of the biopsy scar. Materials and methods: This is a prospective cross sectional study, carried out from May 2003 to March 2005 at Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan. A total of twenty six cases which had undergone either limb salvage surgery or amputation by the Orthopaedic Oncology and Reconstructive Unit, School of Medical Sciences, University Science Malaysia, with the histopathological diagnosis of osteosarcoma were collected. The biopsy tracts were submitted as a whole and examined histologically for tumour presence. Results: Of the 26 cases examined, twenty one cases (80.8%) did not show any tumour infiltration in the biopsy tract. One case (3.8%) had tumour infiltration in the pseudocapsule, two cases (7. 7%) had infiltration to the muscle and another two cases (7.7%) had infiltration up to the subcutaneous tissue. None had skin infiltration.